Opening Schools and Trends in SARS-CoV-2 Transmission in European Countries - Alessandra Buja; Federico Zabeo; Vittorio Cristofori; Matteo Paganini; Tatjana Baldovin; Riccardo Fusinato; Giovanna Boccuzzo; Silvia Cocchio; Silvia Coretti; Vincenzo Rebba; Maria Parpinel (Frontiers Media S.A., 2021)
Objectives: Benefits of school attendance have been debated against SARS-CoV-2 contagion risks. This study examined the trends of contagion before and after schools reopened across 26 countries in the European Union.Methods: We compared the average values of estimated Rt before and after school reopening, identifying any significant increase with a one-sample t-test. A meta-analysis and meta-regression analysis were performed to calculate the overall increase in Rt for countries in the EU and to search for relationships between Rt before schools reopened and the average increase in Rt afterward.Results: The mean reproduction number increased in 16 out of 26 countries. The maximum increase in Rt was reached after a mean 28 days. We found a negative relationship between the Rt before school reopening and its increasing after that event. By 45 days after the first day of school reopening, the overall average increase in Rt for the European Union was 23%.Conclusion: We observed a significant increase in the mean reproduction number in most European countries, a public health issue that needs strategies to contain the spread of COVID-19.